Fly Biology, Ecology, Behavior and Management (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Diptera, known as the “true” flies, is one of the most numerous and diverse orders of insects, comprising about 125,000 species widely distributed throughout the world. These insects play an ecologically relevant role and bear significant importance to humans. Just as certain flies act as pollinators, decomposers, predators, and parasitoids, others are vectors of human diseases and represent serious pests of agriculture, stables, and barnyards. Several dipterans are involved in forensic legal investigations. This Special Issue collects the original research articles and reviews to deepen the biological, ecological, and behavioral knowledge of this diversified insect group and to cover management strategies for both pest and disease vector species. This involves a wide range of studies, such as life history, physiological aspects, reproduction, demographic traits, the ecology and evolution of behavioral patterns, population fluctuation and dynamics, diversity, abundance, trophic relationships, host range and status, natural enemies, integrated pest management, and control tactics.